Do emotions or gender drive our actions? A study of motor distractibility. Issue 1 (1st October 2016) - Ambron, Elisabetta; Rumiati, Raffaella I.; Foroni, Francesco
Abstract : People's interaction with the social environment depends on the ability to attend social cues with human faces being a key vehicle of this information. This study explores whether directing the attention to gender or emotion of a face interferes with ongoing actions. In two experiments, participants reached for one of two possible targets by relying on one of two features of a face, namely, emotion (Experiment 1) or gender (Experiment 2) of a non-target stimulus (a task-relevant distractor). Participants' reaching movements deviated toward the task-relevant distractor in both experiments. However, when attending to the gender of the face the distractor effect was modulated by both gender (task-relevant feature) and emotion (task-irrelevant feature), with the largest movement deviation being observed toward angry male faces. Endogenous allocation of attention toward faces elicits a competing motor response to the ongoing action and the emotional content of the face contributes to this process at a more automatic and implicit level.